Analysis of the Effect of Capital Expenditure, Regional Investment, Labor Absorption, and Economic Growth on Poverty - Novitasari, Riska; Susilo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The reduction in poverty and the high gap between the target and the actual poverty percentage are followed by an increase in capital expenditure, a drastic increase in regional investment in 2022 will not reduce poverty drastically, labor absorption will increase drastically by 3.1%, and economic growth is ranked 3rd. throughout the island of Java. So this research aims to determine the influence of Capital Expenditures, Regional Investment, Labor Absorption, and Economic Growth on Poverty in Central Java Province in 2017-2022. The samples used in this research were 35 regencies/cities in the province of Central Java in the period 2017 to 2022. Data analysis used in this research was multiple linear regression using the T-Test, F Test, and Coefficient of Determination (R2) . The research results show that capital expenditure has a significant positive effect on poverty, regional investment has an insignificant negative effect on poverty, labor absorption has an insignificant negative effect on poverty, and economic growth has a significant negative effect on poverty.